Periodontal Health Condition and Salivary Parameters Among a Group of Patients with Rheumatoid Arthritis in Al- Najaf City (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background: Periodontitis (PD), the most common oral disease, is a destructive inflammatory disease of the teeth supporting tissues and is caused by group of specific microorganisms included: Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythia, and Aggregatibacter actinomycetem-comedias and this condition is categorized by both destruction of connective tissue and alveolar bone due to a chronic inflammation. In periodontitis the clinical findings of bone resorption and the clinical attachment loss around the tooth are a result of inflammatory mediated alterations to remodeling balance of the bone.Material and Method: The samples consist of 60 female participants, 30 were in healthy condition (not suffering from systemic disease and not taking any medication) and 30 with rheumatoid arthritis, with age between (40-45) years. Periodontal status of the two groups was assessed by measuring the probing pocket depth, periodontal attachment loss, plaque index, calculus index and gingival index and salivary sample were collected after subjecting all participants for saliva stimulation and measuring the salivary PH and flow rate for them.Results:  The rheumatoid arthritis(RA) group showed a highly significant  difference in probing pocket depth(PPD), Plaque index(PI),gingival index(GI),calculus index(CAL.I) and loss of attachment(L.A)  compared to Non-RA group, while there is significantly decrease in salivary flow rate  among RA patients when compared to control groups and there is no significant difference in salivary PH between two groups.Conclusion: The results of this study provide evidence of a highly significant relationship between rheumatoid arthritis and periodontal disease this may be due to the similar pathophysiology nature of both diseases.